A construção e representação da identidade indígena nos livros didáticos de língua inglesa - Santos, Rose Hellen de Carvalho (2022)
Recently, scholars and researchers from Applied Linguistics, as well as from other human sciences, have been dedicated to discussing identity. Many of the researches developed in this area of science have demonstrated the importance of discussing the issues of social identities of race, ethnicity, social class, sexuality, gender, etc. both in the scope of social life and in the school setting, more specifically, with regard to the process of teaching and learning foreign languages and the production of textbooks approved by the National Textbook Program (PNLD), which are distributed to all schools public in Brazil. Accordingly, the general objective of the research is to analyze the construction and representation of the identities of indigenous peoples in the high school English language textbooks, approved by the PNLD of 2018. For this purpose, the textbooks will be analyzed from the perspective of an interdisciplinary (MOITA LOPES, 2016) and transgressive (PENNYCOOK, 2016) applied linguistics, as well as by the approach of new literacies, visual and critical literacy (DUBOC, 2017; JANKS, 2017; JANKS, 2016). 2014; JORDÃO, 2017; MENEZES DE SOUZA, 2011; MIZAN, 2012; ZACCHI, 2016d), to understand how the images and verbal representations present in these textbooks seek to promote the visibility and cultural diversity of native peoples. For this, the research will be based on theorists that discuss identity (BAUMAN, 1996, 2005; HALL, 1990, 1996, 2006, 2016; MOITA LOPES, 2002; CASTELLS, 2018), textbooks (MENDES, 2012; SIQUEIRA, 2012; TÍLIO, 2012; FERREIRA, 2012, 2014; PARAQUETT, 2012), and indigenous peoples (RIBEIRO, 1970; CUNHA, 2012; GONZAGA, 2021; MUNDURUNKU, 2020, 2021a; KRENAK, 2020a, 2021). That way, it is carried out research with a qualitative approach, with bibliographic and documentary procedures. During the work, it was observed that although the authors of the collections have sought to construct and represent the identity of the indigenous peoples, it is noticeable that in some cases this attempt by most authors is not only because they understand the relevance of discussing current topics, but due to the fact that they are obliged to follow the requirements of the PNLD public notice of 2015. Thus, it was found that the general objective of the present study, to analyze the formation and representation of the identities of Brazilian indigenous peoples in English Language textbooks, as well as the problem both were answered.